2013
DOI: 10.1586/14760584.2013.824706
|View full text |Cite
|
Sign up to set email alerts
|

Translational sciences approach to RSV vaccine development

Abstract: Respiratory syncytial virus (RSV) is a major cause of lower respiratory tract infections in infants and the elderly. Despite its relatively low degree of antigenic variation, it causes frequent reinfection throughout life. Clinical manifestations of RSV disease and the immune response to infection differ in infants and the elderly, suggesting that vaccines designed to protect these two populations may require different attributes. Here, the authors describe the translational approach of utilizing data from epi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 144 publications
0
11
0
Order By: Relevance
“…In summary, despite some limitations, our inference methodology provides a consistent relation between the incidence of influenza and RSV and the associated hospitalization outcomes, a relation that is linear (proportional) and avoiding parametric assumptions about the weekly hospitalization rates not associated with the two pathogens. The results in our study contribute to the understanding of the hospitalization burden associated with influenza and respiratory syncytial virus, stressing the need for the mitigation of the impact of the annual epidemics corresponding to those two respiratory viruses, including the possibility of developing a vaccine for RSV …”
Section: Discussionmentioning
confidence: 80%
See 2 more Smart Citations
“…In summary, despite some limitations, our inference methodology provides a consistent relation between the incidence of influenza and RSV and the associated hospitalization outcomes, a relation that is linear (proportional) and avoiding parametric assumptions about the weekly hospitalization rates not associated with the two pathogens. The results in our study contribute to the understanding of the hospitalization burden associated with influenza and respiratory syncytial virus, stressing the need for the mitigation of the impact of the annual epidemics corresponding to those two respiratory viruses, including the possibility of developing a vaccine for RSV …”
Section: Discussionmentioning
confidence: 80%
“…The results in our study contribute to the understanding of the hospitalization burden associated with influenza and respiratory syncytial virus, stressing the need for the mitigation of the impact of the annual epidemics corresponding to those two respiratory viruses, including the possibility of developing a vaccine for RSV. 3,30…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Studies have found that the RSV-specific memory CD8 ϩ T cells are reduced in the peripheral blood of healthy elderly adults (10,11), and we have previously shown that RSV-specific IFN-␥ T cell responses are diminished in subjects 65 years and older (12). A number of studies have found that higher neutralizing antibody levels in serum correlate with reduced risk for RSV infection at all ages (13,14); thus, we believe that an effective vaccine in the elderly will need to induce high levels of RSV-neutralizing antibodies and elicit a T helper type 1 (Th1)-like cellular immune response denoted by IFN-␥ production.…”
mentioning
confidence: 88%
“…A live virus vaccine trial has shown that a particular vaccine candidate, MEDI-559, is safe, although effectiveness has not been proven [57]. Other strategies include subunit RSV vaccines, the use of DNAconjugate vaccines to boost antigen presentation, and further development of passive antibody prophylaxis that is focused on F or G proteins [52,[58][59][60][61][62][63][64][65][66][67][68][69][70][71][72]. An additional challenge with all of these strategies is that effective vaccine studies in animals have not been translated into successful human trials.…”
Section: Respiratory Syncytial Virus-how To Develop An Effective Vaccmentioning
confidence: 99%